Laminar Flow Processes of Fluid Energy Carries in Pipe Lines - R. I. Esman; L. I. Shoub (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper proposes methodology for analysis and calculation of laminar fluid flows in pipes and channels.  Various regimes of fluid motion in pipelines of heat-power units and equipment are considered in the paper.The presented dependencies can be used for practical calculations while transporting energy carriers for various application.